Penalizing self-laundering in peru. Is it infringing the principle of ne bis idem? - Flores Mita, Francisco Edgar (2022)
The objective of this paper is to analyze self-laundering in Peru, regulated in the last part of article 10 of Legislative Decree 1106, which literally says: "It can be considered the perpetrator of the crime and therefore subject to investigation and prosecution for asset laundering, anyone who executed or participated in the criminal activities that generated money, goods, effects or profits”. The problem posed is the following: Is it possible to penalize self-laudering behaviors in Peru, without infringing the principle of "Ne bis in Ídem", from the entry into force of article 2 of Legislative Decree 1106, modified by Legislative Decree 1249, that has eliminated the purposes of the asset laundering process? This paper ends proposing a solution for that question.